Blue and red make purple [compact disc] - Gasoi, Jennifer (The Secret Mountain, 2016)
"This beautifully illustrated picture book featuring the irresistible songs of Grammy Award Winner Jennifer Gasoi offers children the opportunity to discover the differet colours of her jazz-inspired music. 'Blue and red make purple' is engaging, playful, and utterly endearing! Included are notes highlighting the history, instruments, and unique characteristics of each musical genre along with activities and listening suggestions...The accompanying CD offers 12 captivating songs that meld many styles including Dixieland swing, bluegrass, folk, Cajun, calypso and klezmer."--Back of book.